Study on using the processes of freestyle skiing and biathlon by their efficiency - Pelin, F.; Cristea, O.; Pelin, G. (The European Proceedings of Social & Behavioural Sciences EpSBS, 2016)
Nowadays, there is an increased, even urgent need for scientific education and training by increasing the theoretical and methodological preparation of all professionals in the cross-country skiing and biathlon field, all the more that we are approaching a new Olympic confrontation. Eliminating the obsolete conceptual means and introducing new ones meet the demands of current cross-country skiing and biathlon competitions. The main goals of this research are the following: to investigate coaches of all the teams participating in World Cup competitions with regard to the free style in cross-country skiing - biathlon and the use of technical procedures in training and competition during the year; to validate the landmarks (coordinates) for the energy consumption and time required to cover the route using the most effective methods for the free technique. One of the ways of access to high performance competitions at the international level for an athlete is also represented by the concern of cross-country skiing and biathlon skiers to find the technical procedure able to expose them to less stress and to ensure the levelling of their heart rate values.